IoT Based Light Intensity Measurement Devices for Indoor Monitoring - Yusof, Izzat Mirza; Mohd Zin, Rosnah (Evolution in Electrical and Electronic Engineering, 2024)
This work focuses on enhancing workplace lighting conditions and occupational safety by leveraging IoT technology. Integrating an IoT system with a prototype luxmeter circuit, efficiently measures light intensity. The use of an LDR sensor detects light presence and absence, while the ESP32 serves as a cost-effective and low-power microcontroller with integrated Wi-Fi capabilities. The ESP32 facilitates data transmission to the Blynk application, allowing real-time monitoring of light intensity in lumen units. The developed method consistently provides accurate measurements, with average percentage differences ranging from 12.31% to 33.61% compared to traditional lux meters. This innovative approach holds promise for ensuring optimal lighting conditions, influencing factors like performance and safety in occupational environments.